2000
DOI: 10.1097/00004872-200018010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bisoprolol and atenolol on endurance exercise capacity in healthy men

Abstract: It is concluded that both drugs affect endurance exercise capacity in young, normotensive men, with a tendency to a smaller reduction during bisoprolol treatment. Haemodynamic variables are unlikely to be involved in the reduction of endurance exercise capacity. The role of the reduced availability of plasma free fatty acids remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 29 publications
6
22
0
2
Order By: Relevance
“…In our subjects, the MLSS occurred at 66% and 67% of P max , indicating no influence of bisoprolol. Vanhees et al (2000) showed that subjects exercising at 70% of P max responded with higher values of LA, supporting their suggestion that cycling at this intensity represented work above the AT. Moreover, this comparison supports the rationale of an individual approach for testing the MLSS.…”
Section: At and Mlss Testmentioning
confidence: 52%
See 3 more Smart Citations
“…In our subjects, the MLSS occurred at 66% and 67% of P max , indicating no influence of bisoprolol. Vanhees et al (2000) showed that subjects exercising at 70% of P max responded with higher values of LA, supporting their suggestion that cycling at this intensity represented work above the AT. Moreover, this comparison supports the rationale of an individual approach for testing the MLSS.…”
Section: At and Mlss Testmentioning
confidence: 52%
“…2) but this difference did not reach statistical significance. Kullmer et al (1987) have found significantly higher LA values, while others have found unchanged (Gullestad et al 1989;Hambrecht et al 1995;Hugson and Smyth 1983;Reybrouck et al 1977;Vanhees et al 2000;Wittke and Kemmler 1999) or decreased LA concentrations (Schnabel et al 1983) during submaximal or maximal exercise tests. A possible explanation for these contrasting findings could be intra-individual differences in LA concentrations that may have been influenced by differences in glycogen stores, nutritional status or daily variation in physiological performance capacity (Aunola and Rusko 1992;Hofmann et al 1994a;Yoshida 1984).…”
Section: At and Mlss Testmentioning
confidence: 96%
See 2 more Smart Citations
“…Bis zum Ausschluss potentiell gefährlicher Arrhythmien sind intensive körperliche Belastungen zu vermeiden. Bei der medikamentösen antiarrhythmischen Therapie gelten die in den jeweiligen Leitlinien festgelegten Grundsätze [8,17]; es sind jedoch die mit der jeweiligen Sportart verbundenen körperlichen und mentalen Belastungsmomente in der Beurteilung des Therapieerfolges zu berücksichtigen [19,20]. Zusätzlich muss berücksichtigt werden, dass unter den antiarrhythmischen Präparaten -Rezeptoren-Blocker in bestimmten Sportarten aufgrund der Dopingbestimmungen nicht zulässig sind.…”
Section: Introductionunclassified